Unlocking Tef Potential: Assessing Yield-Limiting Nutrients Based on Topographic Position in Tehulederie District, Eastern Ethiopia. - Gedamu, Samuel Adissie (International Journal on Food, Agriculture and Natural Resources, 2025)
The fertility status of Ethiopian soil is greatly dynamic across different landscapes. However, fertilizer recommendation is the use of nitrogen and phosphorus regardless of this landscape variation. Fine-tuning fertilizer recommendations and crop yield variability within and between landscapes attracted research attention in Ethiopia and across the globe. A field study was conducted in 2021 in the Tehuledere district of the South Wollo Zone of the Amhara Region to identify major yield-limiting nutrients for tef across three different landscape positions in a catena slope of 0-5%, 5-15%, and >15%. Fertilizer rates of 80, 57,7,30,1 and 0.3 Kg/ha of N, P2O5, S, K20, Zn, and B respectively were evaluated. The randomized complete block design was used. Dunckun's multiple range test was employed for comparison of treatment means for those which were statistically significant. Micronutrients and K didn't impose significant yield differences compared to the recommended nitrogen and phosphorus. The only difference is the control, percentage reduction, and increment in treatments. The study identifies phosphorus (P) and nitrogen (N) as the dominating yield-limiting nutrients in tef production in the Tehulederie district, while micronutrients, potassium, and sulfur contributed nothing to yield. The results showed that raising N and P application rates, particularly to 150% of the recommended rates, significantly increased tef grain yield at all topographic positions, emphasizing the need for optimal fertilizer management. Additional research should be conducted to determine specific rates of N and P application at the study area and other similar agroecologies, further focusing on potential micronutrient deficiencies on hill slopes.